THEORETICAL FOUNDATIONS OF GIS TECHNOLOGIES FOR ASSESSING AGRICULTURAL LAND PRODUCTIVITY AND CONDITION (Modern American Journal of Biological and Environmental Sciences, 2026)
This article examines the conceptual, theoretical, and methodological foundations for the application of Geographic Information Systems (GIS) technologies in the remote assessment of agricultural land productivity and ecological–ameliorative conditions. The study is based on the theoretical principles of systems analysis, cartographic modeling, and digital processing of satellite imagery. Particular attention is given to the role of GIS platforms in soil monitoring, spatial data integration, and the mathematical modeling of productivity indices. The findings demonstrate the potential of GIS technologies to overcome the limitations of traditional soil mapping approaches and to support the development of optimal theoretical models for land resource management. The results indicate that GIS technologies constitute an effective theoretical and functional framework for the early prediction of agricultural land degradation through the integrated analysis of multi-factor soil and climatic data within a unified information system.